Analysis of faecal sludge management in selected urban and peri-urban areas in Chiangmai Province, Thailand - Jula Chaingphukor; Thammarat Koottatep; Shipin, Oleg V.; Ekbordin Winijkul; Royal Thai Government Fellowship (Pathum Thani, Thailand : Asian Institute of Technology, 2019)
This study was result for analysis of FSM practices in urban areas in Chiang Mai by SFD and SAT. The four areas were Chiangrnai city, Mae Ria town, Cheong Doi sub district, and Song K wae sub district. SFD and SAT were that the applications analyzed FSM practices including containment, emptying, transportation, treatment and reuse. The results of SFD presented proportion of safe faecal sludge management and unsafe faecal sludge management. In another application SAT, the assessment was concern about operation of institutions which rely on city government, private operators, local people etc. The FSM practices were assessed by six aspects including infrastructure, regulatory, institutional, capacity, awareness, financial and management. The result can identify the problem of each organization. Overall of FSM practices in four areas, the 56% of faecal sludge was safely managed, and the 44% of faecal sludge was unsafely managed by private providers in Chiangrnai city. In Mae Ria town, the safe faecal sludge management was 34%, and 66% of unsafe management. The faecal sludge in Cheong Doi sub district was 40% of safe management, and the faecal sludge was 60% of unsafe management. In Song Kwae sub district, 39% of faecal sludge was identified as safe management, and 61 % of faecal sludge was identified as unsafe management. All of four areas found that the FSM was controlled by private companies but not all providers were permitted by local governments. Moreover, the problems about the illegal faecal sludge dumping was occurred in all study areas. A one cause of the problems was that the local government was insufficient to enforce the private operators. Another cause was that awareness of institutions was poorly. FSM practices which was inefficient might cause of environmental impacts and heal risk. The water pollution in Chiang Mai was quite clearly which the wastewater from household was directly discharged to water source, and the inefficient storage facilities might cause of the water pollution also.
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Science in Environmental Engineering and Management
Thesis (M.Sc.) - Asian Institute of Technology, 2019
Keywords: Sewage sludge -- Analysis -- Thailand -- Chiangmai; Wastewater -- Treatment; Sewage sludge -- Thailand -- Chiangmai -- Management